Karakterisitik Kimia Mie Kering Bebas Gluten dengan Penambahan Bubuk Daun Kersen - satya, malinda capri nurul; Anna Mardiana Handayani; Findi Citra Kusumasari; Lisus Setyowati (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2024)
Noodles are one of the foods which Indonesian people like. Noodles are generally made from wheat flour which has high gluten content. However, excessive gluten consumption can give an adverse impact on body health, especially for people with celiac disease and Autism Spectrum Disorder (ASD). One gluten-free product is dry noodles with added cherry leaf powder, which has low glucose levels. This research aims to determine the chemical characteristics of dry gluten-free noodles with the addition of cherry leaf powder. This research method uses a Completely Randomized Design (CRD) with two factors studied. The first factor is temperature (S1 : 60° C); (S2 : 70° C); and (S3 : 80° C). The second factor is duration (W1: 90 minutes) and (W2: 120 minutes). Data were analyzed using the Analysis of Variant (ANOVA) statistical test. If there are differences, further analysis was carried out using Duncan's Multiple Range Test 5% statistical test. The result showed that the lowest water content was 9.47% (S3W2), the highest ash content was 2.62% (S3W1), the lowest fat content was 2.17% (S1W1), the lowest protein content was 7.44% (S1W1) and the highest carbohydrate content was 77.70% (S3W2).